2016
DOI: 10.1039/c5ob02061a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel pyrophosphorothiolate-linked dinucleoside cap analogues in a ball mill

Abstract: Michaelis-Arbuzov reactions of S-aryl disulfide derivatives of 3'-thiothymidine or 5'-thioadenosine with tris(trimethylsilyl) phosphite proceeded in high yields to the corresponding phosphorothiolate monoesters. Subsequent hydrolytic desilylation and phosphate coupling were effected in one-pot using liquid-assisted grinding in a vibration ball mill. Novel 3',5'- and 5',5'-pyrophosphorothiolate-linked dinucleoside cap analogues were thereby prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Following Sikchi and Hultin’s original description of nucleoside derivatisation in a low-energy, planetary ball mill [17], commercial, higher energy vibration mills have been used to facilitate established [1821] and unprecedented [22] nucleoside transformations. Remarkably, S N 2 ball-milling chemistry on nucleoside substrates has not, to the authors’ knowledge, been demonstrated, despite reports of similar chemistry on glycoside derivatives [16,23] and α-amino acid analogues [24].…”
Section: Introductionmentioning
confidence: 99%
“…Following Sikchi and Hultin’s original description of nucleoside derivatisation in a low-energy, planetary ball mill [17], commercial, higher energy vibration mills have been used to facilitate established [1821] and unprecedented [22] nucleoside transformations. Remarkably, S N 2 ball-milling chemistry on nucleoside substrates has not, to the authors’ knowledge, been demonstrated, despite reports of similar chemistry on glycoside derivatives [16,23] and α-amino acid analogues [24].…”
Section: Introductionmentioning
confidence: 99%
“…One report describes the mechanosynthesis of dinucleotides, namely Ap n A (with n =2–4), Ap 2 dT and nicotinamide adenine dinucleotide (NAD + ), starting from adenosine 5′‐phosphoromorpholidate, which is rather expensive compared to AMP or needs to be prepared beforehand in solution by using conventional unfriendly methods (Scheme ) . This approach was also applied to the preparation of adenosine diphosphate ribose carbonate derivatives and pyrophosphorothiolate‐linked dinucleoside cap analogues . Although advantageous, this methodology requires the use of costly reagents, namely the phosphoromorpholidate substrate and tetrazole, as well as magnesium chloride.…”
Section: Figurementioning
confidence: 99%
“…[16] This approach was also applied to the preparation of adenosine diphosphate ribose carbonate derivatives [20] and pyrophosphorothiolate-linked dinucleoside cap analogues. [21] Although advantageous, this methodology requires the use of costly reagents, namely the phosphoromorpholidate substrate and tetrazole, as well as magnesium chloride.…”
mentioning
confidence: 99%
“…The groups of Reese (Divakar & Reese, ; Divakar, Mottoh, Reese, & Sanghvi, ; Marriott, Mottahedeh, & Reese, ) and Engels (Jahn‐Hofmann & Engels, ) have described solution‐phase chemistry for the preparation of thionucleosides in which the thiol function is masked by an acid‐sensitive group (e.g., 4‐methoxybenzyl, t ‐butyl, dimethoxytrityl, or thiopixyl) and one‐pot deprotection‐activation is employed, as S ‐aryl disulfides of both nucleoside and peptide substrates under acid conditions have been described. (Divakar et al., ; Schroll, Hondal, & Flemer, ) The application of such disulfides for the preparation of internucleoside phosphorothiolate linkages via Michaelis‐Arbuzov chemistry is well established (Gaynor & Cosstick, ; Li et al., ; Vyle, Li, & Cosstick, ) and was adapted by our group for the preparation of a stable, silylated intermediate (Eguaogie et al., ; Eguaogie et al., ) from which the target pyrophosphorothiolate‐linked dinucleoside analog was accessed using mechanochemistry. In contrast to solution‐phase mixing of reagents and substrates under standard conditions, grinding has only recently been explored in the context of organic chemistry using vibration ball milling (Wang, ), planetary ball milling (Do & Friščić, ), or single‐/twin‐screw extrusion (Crawford, ).…”
Section: Introductionmentioning
confidence: 99%
“…The groups of Reese (Divakar & Reese, 1982;Divakar, Mottoh, Reese, & Sanghvi, 1990;Marriott, Mottahedeh, & Reese, 1990) and Engels (Jahn-Hofmann & Engels, 2004) have described solution-phase chemistry for the preparation of thionucleosides in which the thiol function is masked by an acid-sensitive group (e.g., 4-methoxybenzyl, t-butyl, dimethoxytrityl, or thiopixyl) and one-pot deprotection-activation is employed, as S-aryl disulfides of both nucleoside and peptide substrates under acid conditions have been described. (Divakar et al, 1990;Schroll, Hondal, & Flemer, 2012) The application of such disulfides for the preparation of internucleoside phosphorothiolate linkages via Michaelis-Arbuzov chemistry is well established (Gaynor & Cosstick, 2011;Li et al, 2011;Vyle, Li, & Cosstick, 1992) and was adapted by our group for the preparation of a stable, silylated intermediate (Eguaogie et al, 2016;Eguaogie et al, 2017) from (2); 5 -deoxy-5 -(5nitropyridyl-2-disulfanyl)-adenosine (3); and 5 -thioadenosine 5 -pyrophosphate (P →5 ) adenosine (5). Key: DTNP, 2,2 -dithiobis(5-nitropyridine); BSA, N,O-bis(trimethylsilyl)acetamide; which the target pyrophosphorothiolate-linked dinucleoside analog was accessed using mechanochemistry.…”
Section: Introductionmentioning
confidence: 99%